'Asymmetric revelation' effect: The influence of an increased number of photos on mental imagery and behavioural responses depending on target market. (September 2018) - Larceneux, Fabrice; Bezançon, Marjolaine; Lefebvre, Thomas
There has been little research exploring the effect of the number of photographs used to present a product, and the studies that have been carried out relate to experiments with a reduced number of non-informative photos. This article provides a first field study conducted on 3, 658 real estate ads and shows that an increase in the number of photos decreases favourable behavioural responses for lower range properties, but has no effect in the case of higher range properties. This result is replicated and explained in an experimental study: for lower range properties, the addition of photos deteriorates the valence of mental images, decreases mental self-imagery and increases perceived worry. These variables explain the negative effect of the number of photos on behavioural responses. However, for higher range properties, the addition of photos – informative or not – does not improve behavioural responses. This 'asymmetric revelation' effect depending on the segment of the property market being targeted is discussed.